Honokiol Ameliorates High-Fat-Diet-Induced Obesity of Different Sexes of Mice by Modulating the Composition of the Gut Microbiota - Ding, Yanan; Song, Zehe; Li, Hao; Chang, Ling; Pan, Tingli; Gu, Xueling; He, Xi; Fan, Zhiyong (Frontiers in Immunology, 2019)
Abstract Background Accumulating data support the fact that the gut microbiota plays an important role in the progression of obesity and its related metabolic disease. Sex-related differences are an important consideration in the study of gut microbiota. Polyphenols can regulate gut microbiota, thereby improving obesity and its associated complications. Honokiol(HON), which extract from Chinese herbal medicine, has no studies conducted on its ability to regulate gut microbiota. The aim of this study was to examine whether honokiol (HON) supplementation would improve obesity by regulating the gut microbiota and its related metabolite levels, and whether there were sex-based differences in high-fat diet-induced obese mice. Methods C57BL/6 mice (n=120) were fed a normal chow diet (ND), high-fat diet (HFD), or HFD plus HON at 0.02%, 0.04%, and 0.08% for 8 weeks. Body weight, adipose tissue weight, adipocyte diameter, insulin resistance, blood lipid and serum inflammatory cytokines, gut microbiota and its metabolite were examined at the end of the experiment. Rsults The HON supplementation reduced body weight, adipose tissue weight, adipocyte diameter, insulin resistance, blood lipid and serum inflammatory cytokines levels in HFD-fed mice, and this effect was significant in high dose group. In addition, HON not noly reversed gut disorders in HFD-fed mice, such as by enhanced the abundance of Akkermansia and short-chain fatty acids (SCFAs) producing Bacteroides and reduced Oscillospira but also improved the SCFAs and endotoxin (LPS) levels, although there were sex-based differences. The correlation between several specific genera and obesity-related indexes was revealed through Spearman's correlation analysis. Moreover, HON may have dose dependent effects on regulating gut microbiota to alleviate obesity. Conclusions These findings suggest that HON can prevent diet-induced obesity and its associated diseases by regulating the gut microbiota and improving microbial metabolite levels. Moreover, our findings indicate that sex may be an important factor affecting HON activity.